Tobacco consumption behavior and its associated factors among in-school adolescent students of Saptari, Nepal. - Anil Kumar Mandal (PLOS Global Public Health)
Tobacco consumption among adolescent students in Nepal has grown to an alarming proportion, raising serious concerns about associated factors. The study aimed to describe the tobacco consumption behavior of in-school adolescent students and its associated factors. A cross-sectional survey design was followed to conduct the study. Students of community schools in Class 10 of a municipality in Saptari, Nepal, were the population of the study. All students who were present on the day of data collection participated in the study. Two hundred and twenty-five students participated in the study with a response rate of 95.74%. A validated, self-administered anonymous questionnaire was used to collect data. Frequency, percentage, and binary logistic regression were used to analyze the data. The proportion of students who consumed tobacco was 24% (boy: 18.7%, girl: 5.3%). Sex of students (OR = 5.529, 95% CI 2.375-12.872, P = .000) and tobacco consumption behavior of students' fathers (OR = 3.358, 95% CI 1.308-8.617, P = .012) were significantly associated with tobacco consumption behavior of adolescent students. I concluded that the sex of students and the tobacco consumption behavior of students' fathers are the main associated factors of the tobacco consumption behavior of adolescent students. Anti-tobacco policies should be developed and implemented with the coordination of school administration, the school management committee, and the local bodies targeting students, especially boys and students' fathers.